Grain boundary formation by remnant dislocations from the de-twinning of thin nano-twins. (15th April 2015) - Cao, Y.; Wang, Y.B.; An, X.H.; Liao, X.Z.; Kawasaki, M.; Ringer, S.P.; Langdon, T.G.; Zhu, Y.T.
Abstract : We report a grain boundary formation mechanism in face-centred cubic metals with low stacking fault energies. Severe plastic deformation produces primary nano-twins with a twin boundary spacing of several nanometres, followed by secondary twinning through the activation of Shockley partial dislocations. The partial dislocations interact with primary twin boundaries, resulting in de-twinning of the primary twins and producing very high densities of sessile dislocations. The accumulation of these dislocations produces new grain boundaries with neighbouring grains having similar orientations.